Mating Compatibility and Restriction Analysis of Ganoderma Isolates from Oil Palm and Other Palm Hosts - Chan Jer Jing,; Idris Abu Seman,; Latiffah Zakaria, (Tropical Life Sciences Research, 2015)
Mating compatibility and restriction analyses of Internal Transcribed Spacer (ITS) regions were performed to determine the relations between Ganoderma boninense, the most common species associated with basal stem rot in oil palm and Ganoderma isolates from infected oil palm, two ornamental palms, sealing wax palm (Cyrtostachys renda) and MacArthur palm (Ptychosperma macarthurii), an isolate from coconut stump (Cocos nucifera), Ganoderma miniatocinctum, Ganoderma zonatum and Ganoderma tornatum. The results showed that G. boninense was compatible with Ganoderma isolates from oil palm, G. miniatocinctum and G. zonatum, Ganoderma isolates from sealing wax palm, MacArthur palm and coconut stump. G. boninense was not compatible with G. tornatum. Therefore, the results suggested that the G. boninense, G. miniatocinctum, G. zonatum, and Ganoderma isolates from oil palm, ornamental palms and coconut stump could represent the same biological species. In performing a restriction analysis of the ITS regions, variations were observed in which five haplotypes were generated from the restriction patterns. An unweighted pair-group method with arithmetic averages (UPGMA) cluster analysis showed that all the Ganoderma isolates were grouped into five primary groups, and the similarity values of the isolates ranged from 97% to 100%. Thus, a restriction analysis of the ITS regions showed that G. boninense and the Ganoderma isolates from other palm hosts were closely related. On the basis of the mating compatibility test and the restriction analysis of the ITS regions performed in this study, a diverse group of Ganoderma species from oil palm and other palm hosts are closely related, except for G. tornatum and Ganoderma isolates from tea and rubber.Keserasian mengawan dan analisis pembatasan kawasan Internal Transcribed Spacer (ITS) telah dijalankan untuk menentukan pertalian Ganoderma boninense, spesies yang sering dikaitkan dengan reput pangkal batang kelapa sawit, dengan pencilan Ganoderma daripada kelapa sawit yang dijangkiti, dua palma hiasan iaitu palma pinang merah (Cyrtostachys renda) and palma MacArthur (Ptychosperma macarthurii), pencilan dari tunggul kelapa (Cocos nucifera), Ganoderma miniatocinctum, Ganoderma zonatum dan Ganoderma tornatum. Keputusan kajian menunjukkan G. boninense serasi dengan pencilan Ganoderma dari kelapa sawit, G. miniatocinctum dan G. zonatum, pencilan daripada palma pinang merah, palma MacArthur dan pencilan tunggul kelapa. G. boninense tidak serasi dengan G. tornatum. Oleh itu, keputusan kajian mencadangkan pencilan G. boninense, G. miniatocinctum, G. zonatum, pencilan Ganoderma daripada kelapa sawit, palma hiasan dan tunggul kelapa mewakili spesies biologi yang sama. Analisis pembatasan kawasan ITS menunjukan variasi di mana lima haplotip dijana daripada corak jalur pembatasan. Analisis kluster unweighted pair-group method with arithmetic averages (UPGMA) menunjukkan kesemua pencilan Ganoderma dikelompokkan dalam 5 kumpulan utama dan nilai kesamaan semua pencilan berjulat antara 97% hingga 100%. Dengan itu, analisis pembatasan kawasan ITS menunjukkan G. boninense dan pencilan Ganoderma daripada perumah palma yang lain mempunyai pertalian yang rapat. Berdasarkan ujian keserasian mengawan dan analisis pembatasan kawasan ITS yang dijalankan dalam kajian ini, pelbagai kumpulan spesies Ganoderma daripada kelapa sawit dan perumah palma yang lain, mempunyai pertalian yang rapat kecuali pencilan G. tornatum dan pencilan Ganoderma daripada teh dan getah.